2011
DOI: 10.51724/ijpce.v3i2.195
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Understanding of Graphical Vector Addition in One and Two Dimensions

Abstract: Understanding initial topics in physics (forces, fields, and kinematical quantities) requires a grasp of basic vector concepts. In this study, we intended to explore students’ qualitative understanding of graphical vector addition in one and two dimensions. Using two free-response problems of a diagnostic quiz, one is one-dimensional vector addition and the other is two-dimensional vector addition. Sixty-three grade ten high-school students’ responses were categorized. From the investigation, results represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 7 publications
0
17
1
7
Order By: Relevance
“…The data obtained in the previous study (Wutchana & Emarat 2011) using graphical vector addition indicated some points to simplify the understanding of vector addition. Zavala Genaro et al ( 2010) investigated finding only magnitude of vector, as well as within pedagogical experiments they have used simple tasks.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The data obtained in the previous study (Wutchana & Emarat 2011) using graphical vector addition indicated some points to simplify the understanding of vector addition. Zavala Genaro et al ( 2010) investigated finding only magnitude of vector, as well as within pedagogical experiments they have used simple tasks.…”
Section: Resultsmentioning
confidence: 96%
“…After scrutinizing the results of this questionnaire, it turned out that the leading cause of the problems was their not fully mastering math operations on vectors and not applying them visually. Afterwards, a pedagogical study is carried out to determine the effect of Head-to-tail method, which was considered the best way for vector addition (Wutchana & Emarat, 2011).…”
Section: Figure 1 Comparison Of Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because students' understanding still depends on the representation of the questions. We already know the importance of understanding vectors in studying physics, the teacher must really ensure that students have understood the concept of vectors well [17]. This is because we have understood that students at the university level still experience many difficulties even in vector addition and subtraction operations.…”
Section: The Differences Of Students' Vector Concept Understanding In...mentioning
confidence: 99%
“…With regards to learners' previous experience with vectors in senior-secondary schools, research by (Wutchana & Emarat, 2011) brought out that around 32% of students from senior-secondary schools can give right answers to problems on vector addition after they have been taught vectors in the class. In certain educational institutes of higher learning, the math requirement for the fundamental course in physics is Calculus I, and in some institutions, Calculus II is also a requirement, both of which lack treatment on vectors.…”
Section: Motivationmentioning
confidence: 99%